(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Microwave assist green and effective synthesis of (E)-3-(furan-2-yl)-2-(1H-tetrazol-5-yl) acrylonitrile derivative by Knoevenagel condensation and chemo selective facile intermolecular [2+3] cycloaddition between an azide and a nitrile group in presence of water as a solvent with excellent yields. This approach offers quick purification without using chromatography. Under microwave irradiation, [2+3] cycloaddition has the advantages of clean and straightforward process, mild temperatures, and little environmental effect. The synthetic material performed well in experiments of aggregation-induced emission. Synthesized compound was characterized by NMR, LCMS and FT-IR spectral studies